2022
DOI: 10.1002/cssc.202201320
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Protein‐Based Binder for Lithium‐Sulfur Cathodes Processed by a Solvent‐Free Dry‐Coating Method

Abstract: In the market for next-generation energy storage, lithium-sulfur (LiÀ S) technology is one of the most promising candidates due to its high theoretical specific energy and cost-efficient ubiquitous active materials. In this study, this cell system was combined with a cost-efficient sustainable solvent-free electrode dry-coating process (DRYtraec®). So far, this process has been only feasible with polytetrafluoroethylene (PTFE)-based binders. To increase the sustainability of electrode processing and to decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This special trait of the S/C dry-film cathodes in DD electrolyte was also observed in coin and pouch cells and was already reported in the literature and is linked to the reduction of cathode porosity due to the application of external pressure. [55,56,65] In contrast, this trend is not observed for the other two cathodes, as depicted in Figure 5b. In the fifth cycle, Cath-18/18 yielded a discharge capacity of 592 mAh g(S) À1 , while Cath-7/30 achieved 651 mAh g(S) À1 .…”
Section: Galvanostatic Cycling At Pouch Cell Levelmentioning
confidence: 76%
See 3 more Smart Citations
“…This special trait of the S/C dry-film cathodes in DD electrolyte was also observed in coin and pouch cells and was already reported in the literature and is linked to the reduction of cathode porosity due to the application of external pressure. [55,56,65] In contrast, this trend is not observed for the other two cathodes, as depicted in Figure 5b. In the fifth cycle, Cath-18/18 yielded a discharge capacity of 592 mAh g(S) À1 , while Cath-7/30 achieved 651 mAh g(S) À1 .…”
Section: Galvanostatic Cycling At Pouch Cell Levelmentioning
confidence: 76%
“…Summarizing, it can be stated that the wetting and the swelling of the S/C dry‐film cathodes are governed mainly by the used carbon material, as it was already demonstrated that the swelling of the S/C cathode is not affected by the employed binder. [ 65 ] Additionally it must be considered that the porosity of the cathodes is increased by the swelling as the existing pores are widened and new pores are formed. This additional porosity must be filled with electrolyte and entraps electrolyte, which limits the electrolyte amount available for ion transport between anode and cathode leading to cell failure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry electrode fabrication is an exciting pathway toward sustainable electrode manufacturing that avoids the use of conventional toxic solvents, although the use of polytetrafluoroethylene (PTFE) comes with other challenges. In general, dry electrode fabrication can be classified into three techniques: electrostatic spray dried (ESD) electrodes, , soft template (holey graphene) assisted electrodes, , and fibrillation of the binder. , The ESD method involves an additional high-voltage source, and the scalability of the method is debatable. , The holey graphene-assisted electrode has limitations associated with the additional inactive component and requires high pressure for the electrode roll-to-roll fabrication . The third method is currently the most affordable on a manufacturing scale and requires only slight adjustments in the current manufacturing lines. , By using a fibrillation polymer (e.g., PTFE), the electrode thickness can be tuned without the binder-carbon migration phenomenon which on its own is the main advantage .…”
mentioning
confidence: 99%